Audit of Inpatient Monitoring and Management of Hypoglycemia in Diabetic Patients Compared to National Guidelines - UMAR, ZEESHAN; WAQAR, HAFSA; SHAH, SYED HASSNAIN; WAZIR, SALIHA; ULLAH, HAZRAT; MUKHTIAR, SANA; ULLAH, SAFI; AHMAD, JAMIL; KHAN, KAINAT; HANFI, HANIF ULLAH; Safdar, Sundas; ULLAH, NAQEEB (Pakistan Journal of Medical & Health Sciences, 2025)
Background: Hypoglycemia is a serious and preventable complication in hospitalized diabetic patients, often resulting from treatment with insulin or insulin secretagogues. Effective inpatient monitoring and timely intervention are crucial for minimizing adverse outcomes. Aims: To evaluate current inpatient practices for monitoring and managing hypoglycemia in diabetic patients at Lady Reading Hospital, Peshawar, and to compare these practices with National Guidelines for Management of Hypoglycemia in Hospitalized Patients. Methods: A clinical audit was conducted from July to December 2024, reviewing 150 diabetic patient records with at least one hypoglycemic episode (blood glucose <70mg/dL). Data were collected using a structured proforma aligned with national standards and analyzed using SPSS v25.0. Parameters assessed included monitoring frequency, timeliness of treatment, reassessment, documentation, and preventive strategies. Results: A total of 212 hypoglycemic episodes were recorded. While blood glucose rechecking within 30 minutes post-treatment showed 81.1% compliance, timely treatment initiation within 15 minutes was noted in only 33.5% of cases. Preventive measures and care escalation were documented in just 42% and 29.3% of cases, respectively. Conclusion: Although some aspects of hypoglycemia management at LRH show acceptable adherence to guidelines, significant gaps remain, particularly in early intervention and documentation of preventive strategies.